EAAC1 is expressed in rat and human prostate epithelial cells; functions as a high-affinity L-aspartate transporter; and is regulated by prolactin and testosterone - Franklin, Renty B (BioMed Central, 2006)
BACKGROUND: Prostate epithelial cells accumulate a high level of aspartate that is utilized as a substrate for their unique function of production and secretion of enormously high levels of citrate. In most mammalian cells aspartate is synthesized; and, therefore is a non-essential amino acid. In contrast, in citrate-producing prostate cells, aspartate is an essential amino acid that must be derived from circulation. The prostate intracellular/extracellular conditions present a 40:1 concentration gradient. Therefore, these cells must possess a plasma membrane-associated aspartate uptake transport process to achieve their functional activity. In earlier kinetic studies we identified the existence of a unique Na+-dependent high-affinity L-aspartate transport process in rat prostate secretory epithelial cells. The present report is concerned with the identification of this putative L-aspartate transporter in rat and human prostate cells. RESULTS: The studies show for the first time that EAAC1 is expressed in normal rat prostate epithelial cells, in normal and hyperplastic human prostate glands, and in human malignant prostate cell lines. EAAC1 expression and high-affinity L-aspartate transport are correspondingly down-regulated by EAAC1 siRNA knock down. Exposure of prostate cells to physiological levels of prolactin or testosterone results in an up-regulation of EAAC1 expression and a corresponding increase in the high-affinity transport of L-aspartate into the cells. CONCLUSION: This study shows that EAAC1 functions as the high-affinity L-aspartate transporter that is responsible for the uptake and accumulation of aspartate in prostate cells. In other cells (predominantly excitable tissue cells), EAAC1 has been reported to function as a glutamate transporter rather than as an aspartate transporter. The regulation of EAAC1 expression and L-aspartate transport by testosterone and prolactin is consistent with their regulation of citrate production in prostate cells. The identification of EAAC1 as the high-affinity L-aspartate transporter now permits studies to elucidate the mechanism of hormonal regulation of EAAC1 gene expression, and to investigate the mechanism by which the cellular environment effects the functioning of EAAC1 as an aspartate transporter or as a glutamate transporter.